Experimental study of the transition of two types of wedge gate valves - Korolоv, Оleksandr; Pavlishin, Pavel; Titlov, Olexandr; Mironchuk, Valentin (Technology audit and production reserves, 2019)
The object of research is the type of power valves – gate valve or wedge valve. Gate valves or wedge valves take a leading place among power valve. It has minimal hydraulic resistance, an almost linear dependence of the flow rate on the degree of opening, and is widely used on general-purpose pipeline systems. One of the problem areas of such valves is the loss of tightness or the transition of wedge gate valves. In addition, a more complex design increases the likelihood of failure of such valves. To solve this problem, it is proposed to carry out an experimental study of the gate transition depending on the effort of their closure, as well as research the trend of this dependence. The studies are carried out on a bench that provides air pressure up to 3.0–3.5 MPa and is equipped with cast-iron and brass valves. Air transition is measured in a volumetric manner, displacing water from the measuring cell. To create a force on the rod that closes the valve, we used a KD-230 torque wrench (Russia) are used, which allows to measure torque up to 230 N⋅m. The experimental technique is as follows. The valve is closed with the necessary force wrench, then the compressor was turned on and the required pressure is reached. Air transition is measured by filling the measuring cell over time, fixed by a stopwatch. Processing of the obtained experimental data allows to obtain the following dependences of the relative gap of the valve on the magnitude of the torque for the cast-iron gate valve: Q/√ΔP)=3458∙M(–1,069and for the brass valve: (Q/√ΔP)=6893∙M(–2,435). It is shown that gate valves as well as previously studied valves have one trend: (Q/√Δ)P=С∙M(–g). The degree of torque shows that the larger it is in absolute value, the better the locking characteristics of the valve. So, to ensure the same air transition, the torque on the cast iron valves should have greater values than for the studied brass gate valve.